A study of the fixed and variable capacitances numerical stability in the diffusion and load equation - Ramyi N. ALI; Awni M . Gaftan (Tikrit Journal of Pure Science)
In this paper A study of the fixed and variable capacitances numerical stability in the diffusion and load equation. in two cases , the first when the amplitude is constant the solution is stable , and the second is variable the solution in this case is stable conditionally